The impact of asthma in the school environment and the use of telemedicine - Ana Maria Alexandra Stanescu; Gabriela Carmen Obilisteanu; Laura Carina Tribus; Ioana Veronica Grajdeanu (Amaltea Medical Publishing House, 2022)
Asthma is a common chronic disease in children, especially children from certain ethnic minority groups and those living in poverty. Asthma is also a burden on the health care system, requiring numerous doctor visits, hospitalizations, and urgent interventions, all of which are added to the costs of the treatments. In addition to the burden of symptoms and the high impact due to continuous exacerbations, children with asthma also experience schooling problems. The current therapeutic trend for children with persistent asthma symptoms is to recommend daily preventive anti-inflammatory drugs. In this review, we want to illustrate the impact of asthma in the school environment and the possibility of using interventions for a better quality of life in children with asthma.